A shared history : writing in the high school, college, and university, 1856-1886 - Lueck, Amy J., 1983- (Writing Research, Pedagogy, and Policy Ser., 2020)
"The author demonstrates that public high schools were a vital site for advanced rhetoric and writing instruction in the United States in the nineteenth century. She notes their long-neglected role in the history of composition studies and provides a shared history for secondary and college and university teachers"--